Psychosis Phenomenology, Psychopathology and Pathophysiology - Fukao, Kenjiro (IntechOpen, 2022)
Psychosis has been the central subject of psychiatric research for more than a century and yet it remains an intriguing enigma. This volume reviews the current status of research on psychosis in three different aspects, namely, phenomenology, which is the philosophical/conceptual basis of psychosis; psychopathology, which is the clinical manifestations of psychosis; and pathophysiology, which is the scientific pursuit for the mechanism of psychosis. Chapters focus on schizophrenia, covering such topics as clinical staging, negative symptoms, epigenetics, DNA methyltransferases, and more.